2021
DOI: 10.1002/path.5755
|View full text |Cite
|
Sign up to set email alerts
|

Optical genome mapping identifies a germline retrotransposon insertion in SMARCB1 in two siblings with atypical teratoid rhabdoid tumors

Abstract: In a subset of pediatric cancers, a germline cancer predisposition is highly suspected based on clinical and pathological findings, but genetic evidence is lacking, which hampers genetic counseling and predictive testing in the families involved. We describe a family with two siblings born from healthy parents who were both neonatally diagnosed with atypical teratoid rhabdoid tumor (ATRT). This rare and aggressive pediatric tumor is associated with biallelic inactivation of SMARCB1, and in 30% of the cases, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Currently, sequencing techniques including both NGS-based WGS and long-read sequencing are hampered in unravelling genomic aberrations among highly repetitive sequences that are prone to rearrangements. Evidence has demonstrated that OGM is more efficient than long-read technology for characterising structural rearrangements with larger median and average sizes, as well as complex regions, such as nucleolar organiser regions and transposable elements 5 10 43 44. The main limitation of OGM currently is the missing labels in the centromeric regions, which causes some chromosomal rearrangements such as Robertsonian translocations to be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, sequencing techniques including both NGS-based WGS and long-read sequencing are hampered in unravelling genomic aberrations among highly repetitive sequences that are prone to rearrangements. Evidence has demonstrated that OGM is more efficient than long-read technology for characterising structural rearrangements with larger median and average sizes, as well as complex regions, such as nucleolar organiser regions and transposable elements 5 10 43 44. The main limitation of OGM currently is the missing labels in the centromeric regions, which causes some chromosomal rearrangements such as Robertsonian translocations to be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Given the known benefits of HiFi-GS in SV detection, we pursued HiFi-GS in unsolved rare diseases beyond earlier demonstration studies as routine streamlining of trios. 18,19 Early results from HiFi-GS showed the expected improvement in detection rates for SVs but also provided first glimpses of diagnostic variation currently only achievable through HiFi-GS, such as the discovery of novel repeat expansions (including repeat size and sequence composition), the solving of CNV breakpoints and orientation/localization, and the resolution of phase in the absence of parental samples. The potential for having full genome analyses by HiFi-GS was explored in this study as proof of concept; further work will elaborate underexplored areas of HiFi-GS utility, such as personal assemblies, haplotype-phasing, and directed work on duplicated gene regions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent technological advances in long-read platforms enable the consideration of lrGS for unsolved rare diseases. 19 In this study, we leveraged a large-scale pediatric genomic medicine program with real-time return of results to explore automation of variant prioritization and expert clinical interpretation, as well as the retesting of prior negative exomes at a scale that has not been previously reported. The results from the analyses of >1000 patients with rare disease highlight the utility of systematic variant prioritization, identify variants in blind spots associated with current technologies, and underscore the imperative for improved sharing strategies of suggestive results across rare disease programs and cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…One such germline variant was identified as an SVA in a pair of siblings diagnosed with the disease. 59 The SVA was located in intron 2 of the gene, which caused splicing from exon 2 into the SVA using a splice acceptor in the Alu -like region. This is likely a highly penetrant variant due to both siblings being affected, and the insertion only present in the mother in a mosaic state.…”
Section: Sva-induced Aberrant Splicingmentioning
confidence: 99%
“…This is likely a highly penetrant variant due to both siblings being affected, and the insertion only present in the mother in a mosaic state. 59 The final example of an exonized SVA in disease is located in the GAA gene and is associated with Pompe disease, an autosomal recessive lysosomal storage disorder. 49 The patient was homozygous for an insertion in intron 15 of GAA gene, which caused exon 15 to be spliced into the SVA and termination of the transcript at the insertion’s poly A-tail and the almost complete absence of the full-length isoform.…”
Section: Sva-induced Aberrant Splicingmentioning
confidence: 99%